Ownership structures, operating performance and productivity in Indonesia and Malaysia - Sukmadilaga, Citra (2013)
The relationship between ownership concentration and company performance has been an issue of interest among academics, investors, and policy makers because of the key issue is in understanding the effectiveness of family and state ownership that serves as a control mechanism. This study focused on analyzing two types of ownership adopted from Claessens, et al. (1999), namely family and state owned enterprises. It examined the impact of family and state ownership on firm performance in selected emerging market. In a more specific manner, this study attempted to address the following question: Do different ownership structures lead to different performance? To date, there are a few studies on the economic and financial performance of firms associated with family owned (FOEs) and state owned enterprises (SOEs) in Indonesia and Malaysia. Understanding the firms’ performance will help the state and stockholders to draft policies in order to overcome weaknesses and ensure that the market and stockholders investments are protected. Agency problems tend to arise in many ways that can be a cause in wealth of shareholders and/ or bondholders since this affects firm’s performance. So far, there are still many inconclusive findings about whether family and state ownership give positive or negative impact on firm’s performance. This study employed Malmquist Productivity Index as economic performance measurement while abnormal operating performance used as financial performance. Abnormal operating performance chosen because, according to Barber and Lyon (1996), it is calculated by using operating income despite of earning per share. Operating income has advantages compared to earnings in two aspects. First, since operating performance can be obscured by special items, tax considerations, or the accounting for minority interests, Barber and Lyon argued that operating income is a cleaner measurement than earnings of the productivity of operating assets. Second, researchers often study corporate events that result in changes in capital structure. Such changes affect interest expense and, consequently, earnings net of interest expense, but leave operating income unaffected (assuming that the capital structure changes do not affect the firm’s operation). Meanwhile in terms of productivity, according to Griffel, et al. (1996), the Malmquist index does not require the profit maximization or cost minimization assumption. This assumption is particularly relevant for SOEs, as most of the firms under state ownership do not necessarily follow the objective of profit maximization. Secondly, it is the preferred method when input and output price information are not available or could be distorted due to regulatory practices. Lastly, the use of non-parametric strength of DEA, which does not require a parametric functional form on the technology, can handle multiple input and output characteristics of various industries in which the sample firm operate. This study used a sample that classified as family and state ownership that listed in Indonesia Stock Exchange and Bursa Malaysia. Furthermore, to define their performance, matched sample was needed which base on similar SIC Code and size of company. Period of study is from 1992 to 2007 and was divided into three sub-periods which is before Asian crisis (1992-1996), during Asian crisis (1997-2000), and after Asia crisis (2001-2007). Technical efficiency study in Indonesia showed that SOE had better performance than FOE since SOE’s performance increased more stably during research period. This result is parallel with productivity index research result where Indonesia’s SOE exhibited higher productivity than FOE due to the SOE’s significant productivity index enhancement. Moreover this study also revealed that FOE’s productivity index increase came from new technology adoption while the increase of SOE’s productivity index was resulted from efficiency change enhancement of several SOE samples. Meanwhile Malaysia-based technical efficiency study demonstrated that FOEs samples had lower efficiency level than SOEs, which performed little enhancement. During crisis period, the Government supported this enhancement by giving some privileges to SOEs such as lower investment and export financing costs, as well as their preferences to the buying and selling. However the increase from both company types showed no significance statistically. According to productivity study in Malaysia, some FOEs samples during crisis period demonstrated productivity increase that might be caused by both early recovery from crisis effects and new technology adoption. SOEs samples performed constant enhancement due to the Malaysian government implementations of capital restructuration and fiscal initiative expansion to several SOEs. Therefore based on this study, both Malaysia’s FOE and SOE were productive and statistically significant. Indonesian Family-owned Enterprises had become more productive during three sub-periods. An observation found that there was a slight increase due to the additional sample companies in crisis period. With further analysis, this study found that the increase was caused not only by additional sample, but also by acquiring new technology for some companies that contributes to the increase of productivity index. When Indonesian State-owned Enterprises was analyzed, the finding revealed that State-owned Enterprises had improved significantly from time to time within the three sub-periods. In contrast with Family-owned Enterprises sample, State-owned Enterprise revealed that the increasing productivity index during crisis was resulted from the increase in efficiency changes from some sample companies, by increasing their market share and their sales. With regards to productivity, Malaysian Family-owned Enterprises had slightly increased during three sub-periods. From further analyses, the increase during crisis was merely due to some additional samples of companies included in crisis periods. This action led to the increasing of productivity index. Further explanation could be derived from an observation from some of highest productivity index, such as White Horse Berhad and Latitude Tree Holding Berhad. Both of them had early recovery since Malaysian government released Government’s Second Industrial Master Plan for the 1998 to 2006 period. In 1999, both companies boosted their research and development divisions to create new products with innovative designs. The increase of frontier shift contributed to the increase in productivity index. In closer look, for State-owned Enterprises, the finding revealed that State-owned Enterprises had improved from time to time within the three sub-periods. The productivity increase was due to capital restructuring and the expansionary fiscal initiatives implemented by the Malaysian Government for SOEs such as Tenaga Nasional Berhad and Time Engineering Berhad. In terms of abnormal operating performance, the combination result between adjusted R2 and non-parametric Wilcoxon test statistic revealed that Indonesia Family Owned Enterprises had model 1 (Level of industry performance with two digit SIC matched) as the most explanatory power in detecting abnormal operating performance. Meanwhile, the result for Indonesian State Owned Enterprises showed that model 6 (Lagged firm performance and change in industry performance with two-digit SIC and size matched) is the model with the most explanatory power that uses lagged firm performance and change in industry performance. In analyzing sub-periods, Indonesian Family Owned Enterprises result showed positive number during pre-crisis, crisis, and post-crisis periods. These positive numbers reflected that Indonesian Family Owned Enterprises sample were outperformed if compared to average mean of their industry. However, the mean showed a declining trend due to the companies’ slow recovery from the crisis, particularly companies that run property industry. Meanwhile with Indonesian State Owned Enterprises sample, model 6 showed positive number for pre-crisis and crisis periods, but in post-crisis, model 6 gave negative number. Positive number means that sample firms showed abnormal operating performance and outperformed than their average industry. Moreover, negative value in post-crisis period came from two firms namely PT. Kimia Farma Tbk and PT. Indo Farma Tbk. Summary for Malaysian abnormal operating performance, based on the adjusted R2 and non-parametric Wilcoxon test statistic result revealed that Family Owned Enterprises had model 5 (Lagged firm performance and change in industry performance four digit SIC matched) as the most explanatory power in detecting abnormal operating performance. Finding from pre-crisis and post-crisis periods showed negative values. These results indicated that although Malaysian Family Owned Enterprises had abnormal operating performance, they still underperformed if compared to industry average especially industry with similar four-digit SIC code. As for the State Owned Enterprises, the result showed that model 3 (Level of industry performance with two-digit SIC and size matched) is the model with the most explanatory power level of industry performance. The result showed positive value during three sub-periods. The positive value indicated that Malaysian State Owned enterprises outperform their average industry. Further observation in sub-periods, Malaysian Family Owned Enterprises result showed model 5 gave negative number during pre-crisis and post-crisis periods. These results gave implication that Malaysian Family Owned Enterprises had abnormal operating performance and underperform when compared to industry average especially industry with similar four-digit SIC code. The data revealed that most of sample firms which underperformed were companies that run property industry. Meanwhile, in crisis period model 5 gave positive figure which revealed that sample firms outperform. The reason behind this finding is due to several companies within the sample recovered early from crisis; hence these several companies contributed to increase of mean. Sub-period analysis for Malaysian state Owned Enterprises showed that nothing special happened. The average means depict positive figure during three sub-periods. As expected before, calculation the average means during crisis declined, possibly because of the decreasing performance of the Malaysian State Owned Enterprises. However, overall performance of Malaysian State Owned Enterprises outperformed their industry. This result of this study has implication as follows: 1) Family Owned Enterprises should think strategically how to compete with State Owned Enterprises especially if they are competing in similar industry. 2) For each type of ownership which have model that have influenced by changing in their internal company or changing within their industry, they should considering all factors that can impact their performance.